1999
DOI: 10.1073/pnas.96.23.13118
|View full text |Cite
|
Sign up to set email alerts
|

Identification of eukaryotic mRNAs that are translated at reduced cap binding complex eIF4F concentrations using a cDNA microarray

Abstract: Although most eukaryotic mRNAs need a functional cap binding complex eIF4F for efficient 5 end-dependent scanning to initiate translation, picornaviral, hepatitis C viral, and a few cellular RNAs have been shown to be translated by internal ribosome entry, a mechanism that can operate in the presence of low levels of functional eIF4F. To identify cellular mRNAs that can be translated when eIF4F is depleted or in low abundance and that, therefore, may contain internal ribosome entry sites, mRNAs that remained a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
297
4
3

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 350 publications
(319 citation statements)
references
References 26 publications
15
297
4
3
Order By: Relevance
“…The additional bands of proteins in the Western blot analysis may represent products of degradation of the eIF4G-1 protein. 15 However, there is an overall good correlation between the results from the Western blot analysis and the immunohistochemistry. The immunohistochemic staining method has the advantage of being able to localize the protein, and therefore the cytoplasmic localization of the translational factor eIF4G-1 184 was confirmed.…”
Section: Discussionmentioning
confidence: 89%
“…The additional bands of proteins in the Western blot analysis may represent products of degradation of the eIF4G-1 protein. 15 However, there is an overall good correlation between the results from the Western blot analysis and the immunohistochemistry. The immunohistochemic staining method has the advantage of being able to localize the protein, and therefore the cytoplasmic localization of the translational factor eIF4G-1 184 was confirmed.…”
Section: Discussionmentioning
confidence: 89%
“…Polysome profiling has been carried out under a number of conditions when cap-dependent translation has been inhibited including following polioviral infection, 30,31 during mitosis, 32 hypoxia and apoptosis (our unpublished data). In each of these diverse conditions, it has been found that approximately 3% of the messages remain associated with the polysomes including c-myc mRNA.…”
Section: Analysis Of Mrnas That Remain Polysomally Associated During mentioning
confidence: 99%
“…All bicistronic constructs had the respective 5 0 UTR sequences cloned between Rluc and Fluc genes, in pCDNA3.1, which does not contain a chimeric intron. p53 5 0 UTR sequences were also cloned downstream of the inactive DEMCV IRES sequence in the intercistronic region of the plasmid pRDDEF (Johannes et al, 1999). The DEMCV sequence was also cloned upstream of Rluc gene in the bicistronic plasmids.…”
Section: Methodsmentioning
confidence: 99%
“…These results indicated the presence of IRES elements in both p53( þ 39) and (À1) sequences. To rule out the ribosomal read-through of the intercistronic sequences, they were cloned in the plasmid pRDEF, downstream of a stable RNA structure derived from the encephalomyocarditis virus (EMCV) IRES that inhibits ribosomal read-through (Johannes et al, 1999). These bicistronic DNAs, pRDEp53( þ 39)F and pRDEp53(À1)F, produced 13-and 12-fold higher Fluc activity, respectively, than that from the control vector pRDEF (Fig 2B(ii)).…”
Section: P53 5 0 Utr Sequences Contain Iressmentioning
confidence: 99%